Penguatan Pendidikan Karakter melalui Peningkatan Logika, Etika, dan Estetika di MTs. Al-Ma’arif dan MA Al-Ma’arif, Dusun Cumpleng, Desa Brengkok, Kecamatan Brondong, Kabupaten Lamongan - Fahmi, Arif; Sofiyah, Kharisma; Rohman, M. Fathor; Zaini, Ahmad Afan; Muhyidin, Muhyidin (Santri : Journal of Student Engagement, 2025)
The existence of institutions from time to time is increasingly eroded by waves of 'levelling' in the name of accreditation. As an effort to defend his vision against the eroding of civilization, the author took the initiative to hold character education seminars at the Al-Ma'arif Foundation, Dusun Cumpleng, Brengkok Village, Brondong District. The goal to be achieved is the formation of students who have intact and balanced character between mind and heart, are intelligent, have good ethics, are physically and spiritually intelligent, have skills and morals, as well as cognitive, affective and psychomotor. In this service prepare the process a character education process and management that reflects management steps, implementation strategies, educational and educational HR readiness, indicators of program success, comprehensive program design containing content and contextual analysis of the educational process, program evaluation and monitoring techniques and policy formulation. . This assistance uses the PAR (Participatory Action Research) method, which is a research methodology that invites individuals and communities to actively participate by following activities in the same construction or facility with the knowledge they have. In its implementation there are several stages, namely analyzing the problem, compiling program planning, program implementation and program evaluation. Character education can be done early on in any institution or foundation. Character education is carried out and applied to Senior High School and Junior High School Al-Ma'arif students in Cumpleng Hamlet, Brengkok Village, Brondong District.